Family and behavioral predictors of school problems in junior and high school students - Frías Armenta, Martha (2001)
A model of family influences on the development of antisocial behavior and scholar problems in adolescents is presented. Two-hundred four students of junior and high school were assessed. Data were analyzed through a structural equation model. Results showed that child abuse, a no cooperative family and mothers' alcohol consumption had a direct effect on antisocial behavior,which in turn promoted delinquen behavior and negatively affected school grades of students. Delinquency and mothers' alcohol consumption had an influence on students' school problems,which could be partially overturned by their social abilities. Results suggest the necessity of counselling for families in arder to prevent school problems and bad grades in adolescents.